Polyoxometalate‐Soft Matter Composite Materials: Design Strategies, Applications, and Future Directions. (31st October 2022) - Kruse, Jan‐Hendrik; Langer, Marcel; Romanenko, Iuliia; Trentin, Ivan; Hernández‐Castillo, David; González, Leticia; Schacher, Felix H.; Streb, Carsten
Abstract: Molecular metal oxides or polyoxometalates (POMs) offer unrivaled properties in areas ranging from catalysis and energy conversion through to molecular electronics, biomimetics, and theranostics. While POMs are ubiquitous metal oxide model systems studied in most areas of chemistry and materials science, their technological deployment is often hampered by their molecular nature, as this leads to increased degradation, leaching, and loss of reactivity, particularly when harsh applications, such as water electrolysis, thermal catalysis or highly basic/acidic reaction solutions are targeted. Therefore, immobilization of POMs on heterogeneous substrates has recently become a central theme in POM research. While early studies focused mainly on metal oxide and semiconductor supports, more recently, POM integration in soft matter matrices including polymers, conductive polymers, hydrogels, and stimuli‐responsive matrices leads to breakthroughs in multifunctional composite design. This Review summarizes pioneering experimental and theoretical progress in this emerging field over the last decade, highlighting current challenges that need to be overcome to allow a more widespread technological deployment and providing the authors' view of some of the most promising future directions of the research field. In addition, the current understanding of correlations between structure (on the molecular, nano‐ and microscale) and reactivity in POM polymer composites is summarized, so that rational materials design can be further developed. Abstract : This review explores recent progress, current challenges and future directions of molecular metal oxide clusters embedded in functional polymers.